Structural alterations of polycarbonate/PBT by gamma irradiation for high technology applications. Issue 4 (16th February 2016) - Zaki, M. F.; Elmaghraby, Elsayed K.; Elbasaty, A. B.
Abstract: In this work, polycarbonate/polybutylene terephthalate (PC/PBT) was irradiated with different gamma doses ranging from 200 kGy to 1950 kGy. Structural alterations of irradiated PC/PBT polymer blend have been studied using UV–vis spectroscopy, X-ray diffraction, and Fourier transform infrared (FTIR), as well as surface wettability. The results of UV–vis spectra showed that gamma irradiation induced an increase in the optical absorption with an increase in the gamma doses with shift in the optical absorption edge in the irradiated samples toward the higher wavelength. This shift is correlated with the decrease in optical band gap energy. Optical band gap decreases up to 12 and 20% with respect to pristine sample for direct and indirect transition, respectively. The number of carbon atoms per conjugated length has been estimated. The α phase and β phase of the crystalline PBT structure were observed. The α phase reflections are slightly increased due to the irradiation but the accompanying α to β transformation alters the results. FTIR investigation showed slight variation in the absorption spectrum specially in the range from 1300 to 1001 cm −1 which are related to the O–C–O arrangements that is found to be the most affected part of the molecule by irradiation. A remarkable increase was observed in the wettability, surface free energy, and adhesion work of irradiated samples with an increase in the gamma doses.